Exploiting 20Ne isotopes for precision characterizations of collectivity in small systems - Giacalone, Giuliano; Bally, Benjamin; Nijs, Govert; Shen, Shihang; Duguet, Thomas; Ebran, Jean-Paul; Elhatisari, Serdar; Frosini, Mikael; Lähde, Timo A.; Lee, Dean; Lu, Bing-Nan; Ma, Yuan-Zhuo; et al. (Physical review letters, 2025)
Whether or not femto-scale droplets of quark-gluon plasma (QGP) are formed in so-called small systems at high-energy colliders is a pressing question in the phenomenology of the strong interaction. For proton-proton or proton-nucleus collisions the answer is inconclusive due to the large theoretical uncertainties plaguing the description of these processes. While upcoming data on collisions of 16O nuclei may mitigate these uncertainties in the near future, here we demonstrate the unique possibilities offered by complementing 16O+16O data with collisions of 20Ne ions. We couple both nuclear lattice effective field theory (NLEFT) and projected generator coordinate method (PGCM) ab initio descriptions of the structure of 20Ne and 16O to hydrodynamic simulations of 16O +16O and 20Ne +20Ne collisions at high energy. We isolate the imprints of the bowling-pin shape of 20Ne on the collective flow of hadrons, which can be used to perform quantitative tests of the hydrodynamic QGP paradigm. In particular, we predict that the elliptic flow of 20Ne+20Ne collisions is enhanced by as much as 1.174⁢(8)stat⁢(31)syst for NLEFT and 1.139⁢(6)stat⁢(39)syst for PGCM relative to 16O +16O collisions for the 1% most central events. At the same time, theoretical uncertainties largely cancel when studying relative variations of observables between two systems. This demonstrates a method based on experiments with two light-ion species for precision characterizations of the collective dynamics and its emergence in a small system.
Im Text ist "20" hochgestellt
Gesehen am 02.12.2025